Influential factors and willingness to advocate for HPV vaccination among male nursing interns in China - Huizi Wang; Fei Liu; Hui Zhang; Ning Chen; Chen Wang (BMC, 2024)
Abstract Background Human papillomavirus (HPV) infection significantly contributes to the global cancer burden. Understanding the factors influencing male clinical interns' willingness to promote HPV vaccination is crucial for developing effective public health strategies in China. Methods This study employed a stratified random sampling method to select 1,980 male clinical interns from five provinces in China between January and March 2024. Data were collected on participants' demographic characteristics, HPV-related clinical experience, and knowledge. The Theory of Planned Behavior framework, encompassing attitudes, subjective norms, and perceived behavioral control, was used to examine factors influencing the willingness to promote the HPV vaccine. Logistic regression analyses were conducted to identify factors associated with the willingness to promote the HPV vaccine. Results Among the respondents, 72.29% were willing to encourage others to receive the HPV vaccine. Significant factors influencing this willingness included older age (OR = 3.065, P ≤ 0.001), higher monthly household income (OR = 1.449, P = 0.025), participation in the diagnosis and treatment of HPV-related diseases (OR = 3.458, P ≤ 0.001), positive attitude towards the vaccine (OR = 13.503, P = 0.004), and strong perceived behavioral control (OR = 2.364, P = 0.006). Conclusion This study highlights the critical role of practical experience and targeted education in promoting HPV vaccination among male clinical interns in China. Enhancing the training and education of this group is essential for improving HPV vaccine advocacy and supporting public health efforts to reduce HPV-related diseases.